004 Survival analysis of lower-limb apophyseal injuries in youth elite soccer in association with growth and skeletal maturation. (3rd March 2020) - Materne, Olivier; Farooq, Abdulaziz; Chamari, Karim; Johnson, Amanda; Weir, Adam; Hölmich, Per; Greig, Matt; Naughton, Lars Mc
Abstract : Background: Adolescent athletes have different injury patterns to those of adults, and their growing bones are susceptible to overuse injuries. Evidence of growth-related injuries in relation to growth and maturation in youth elite soccer players remains sparse. Objective: 1) to investigate lower-limb apophyseal injuries (LL-AI) and 2) their relationship with peak height velocity (PHV) and skeletal age (SA) in elite young soccer players. Design: Prospective longitudinal cohort study. Setting: Youth elite soccer academy. Patients (or Participants): During 4 consecutive seasons, 551 youth soccer players from under U-9 (under 9 yrs.) to U-19 with a mean age of 14.9±1.7 years participated. Interventions (or assessment of risk factors): Injury surveillance Main outcome measurements: Lower-limb apophysis items were integrated in the consensus injury registration form. Diagnoses were established by experienced clinicians and the team's dedicated physiotherapist. Imaging was utilized if required. Skeletal age was assessed at the start of each season (Fels method), then classified by maturity status (SA minus chronological age: Late: >-1 yr; Normal: ±1 yr; Early: <1 yr & SA<18 yr; Mature: SA=18 yr). Peak height velocity was calculated non-invasively (Mirwald method) three times during each season, then allocated to Pre-circum <-1 yr from PHV), Circum- (≥-1 yr from/to PHV ≤+1) or Post-circum (>1 yr to PHV) status. Results: There were 307 (14% of 2204) growth-related injuries recorded, of which 84% were LL-AI. After controlling for confounders, adjusted injury-free survival analysis showed substantially different hazard ratios (HR) for LL-AI (i) PHV: Circum higher than Pre-circum (HR: 2.09, 95% CI, 1.22–3.56; p<0.05) and Post-circum (HR: 1.88, 95% CI, 1.22–2.90; p<0.05) respectively. (ii) SA: Mature lower than Late-maturers (HR=2.56, 95% CI: 1.01–6.51; p<0.05), Normal-maturers (HR=2.14, 95% CI: 1.30–3.50; p<0.05) and Early-maturers (HR=1.82, 95% CI: 1.11–2.97; p<0.05) respectively. Conclusions: Apophyseal injuries of the lower-limb is the most prevalent growth-related injury in youth soccer. The growth spurt was the period of greatest risk for apophyseal injury. However, the type and location of apophyseal injuries varies depending on growth and skeletal maturation status.